Finished Paint Warehouse Re-Layout Using Slp and Shared Storage Methods to Minimize Material Handling Costs - Riqi Hidayatulloh; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2022)
Re-Layout finished paint warehouse use method Systematic Layout Planning (SLP) and Shared Storage could reduce wastage caused by layout lack of facilities max, for example distance long distance cause fare material handling Becomes big and heaps or paint arrangement that is not efficient.From result study Re - layout done use method Systematic Layout Planning (SLP) and Shared Storage obtained results efficiency as much as 59.74% of distance initial 25,967 m to 10,452 m after use layout proposal and that take effect to results fare material handling every company month can spend Rp. 5,959.99.12 for layout beginning be Rp. 2,817,056.32 per month after use proposal layout so that can save as much as 52.27%